2019
DOI: 10.1007/978-3-030-27731-4_17
|View full text |Cite
|
Sign up to set email alerts
|

Towards Measuring the Amount of Discriminatory Information in Finger Vein Biometric Characteristics Using a Relative Entropy Estimator

Abstract: This chapter makes the first attempt to quantify the amount of discriminatory information in finger vein biometric characteristics in terms of Relative Entropy (RE) calculated on genuine and impostor comparison scores using a Nearest Neighbour (NN) estimator. Our findings indicate that the RE is system-specific, meaning that it would be misleading to claim a universal finger vein RE estimate. We show, however, that the RE can be used to rank finger vein recognition systems (tested on the same database using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…A study on the individuality of finger vein templates [304] analysing large-scale datasets and corresponding imposter scores showed that at least the considered finger vein templates are sufficiently unique to distinguish one person from another in such large scale datasets. This book contains a chapter [128] on assessing the amount of discriminatory information in finger vein templates. Fusion has been considered in multiple contexts.…”
Section: Finger Vein Recognition Toolchainmentioning
confidence: 99%
“…A study on the individuality of finger vein templates [304] analysing large-scale datasets and corresponding imposter scores showed that at least the considered finger vein templates are sufficiently unique to distinguish one person from another in such large scale datasets. This book contains a chapter [128] on assessing the amount of discriminatory information in finger vein templates. Fusion has been considered in multiple contexts.…”
Section: Finger Vein Recognition Toolchainmentioning
confidence: 99%